CORRELATIONS OF APPLICATION OF PACTA SUNT SERVANDA LEGAL PRINCIPLES AND PERMITTED CAUSAL RELATIONS - Michael Nainggolan; Djoni S Gozali; Rachmadi Usman (Universitas Muhammadiyah Tapanuli Selatan, 2023)
The purpose of this research is to find out and analyze the legal consequences of articles that are contradictory or inconsistent with the legal principles in the agreement in Law no. 7 of 2011 concerning Currency and to find out and analyze the relationship between the legal principles of Pacta Suntc Servanda and the non-prohibited cause at statute no. 7 of 2011 concerning Currency in its application. The research method used is normative legal research The research result are: first, that the emergence of legal consequences from the existence of an inconsistency in the application of the principle of contract law contained in Law no. 7 of 2011 concerning Currency, creates inconsistencies in the application of legal norms. Second, that Article 23 substantially stipulates a prohibition against the use of the Rupiah currency, but on the one hand it can be applied the other way around. That reviewing from Jurisprudence No. 1/Yur/Pdt/2018, which states: “With the consistent compliance with the plaintiff's claim to the defendant to pay a sum of money in foreign currency, the court's order that grants the petition must comply with Article 21 Paragraph (1) of Law no. 7 of 2011 by adding the formulation of words which in essence “payments must be made in rupiah in accordance with the middle rate of exchange of Bank Indonesia at the time of execution of the decision. Third, Every person in entering into an engagement through an agreement or contract which in the agreement uses a foreign currency calculation, must also include in the agreement or contract the value of the payment obligation in rupiah currency at the time the agreement or contract is executed, so that there is no problem with the payment in the future and also correlates the legal terms of an agreement in the principle of a lawful clause so that the agreement is not legally flawed and/or even null and void by law itself